Students' Ability in Writing Descriptive Text of the Tenth Grade Year Students' of SMKN 6 Surakarta in 2015/2016 Academic Year - Apriliansyah, Richo Dwi, Drs. Djoko Srijono, M.Hum (2016)
This research is aiming on 1) To describe the students' ability in writing descriptive text at the tenth grade of SMK N 6 Surakarta in 2015/2016 academic year and 2)To know the problems faced by the tenth grade students of SMK N 6 Surakarta in writing descriptive text. In this research, the researcher uses a descriptive qualitative as the type of the research. The object of the study is the students' ability in writing descriptive text at the tenth grade of SMK N 6 Surakarta in 2015/2016 academic year. The data of this research are English teacher of SMK N 6 Surakarta and the sentence of descriptive text written by the tenth grade students of SMK N 6 Surakarta 2015/2016 academic year. The technique for analyzing data is 1) Collecting the data taken from observation and interview, 2) Analyzing the data based on the five criteria of writing descriptive text: grammar, vocabulary, content, mechanic and organization. The results show that the students' ability in MM 1 class in writing descriptive text at the tenth grade MM 1 Class of SMK N 6 Surakarta in 2015/2016 academic year is Fair. 9 students belong to good category (the score 17-15) or 29,03%. 23 students belong to fair category (the score 14-12) or 74,19%, and there is no student who belongs to very good and poor category. In the other class, The students' ability in writing descriptive text at the tenth grade MM 2 Class of SMK N 6 Surakarta in 2015/2016 academic year is Fair. 13 students belong to good category (the score 17-15) or 40,62%. 19 students belong to fair category (the score 14-12) or 59,37%, and there is no student who belongs to very good and poor category.